A risk profile of elite Australian athletes who use illicit drugs - Dunn, M.; Thomas, J. A. (Addictive Behaviors, 2012)
Much of the literature investigating the relationship between sports participation and substance use has focused upon student populations, with little focus being given to athletes who participate at elite levels. Identifying why some athletes may be at a greater risk for substance use can help in the design and implementation of prevention initiatives. Data for the current study was from 1684 self-complete surveys with elite Australian athletes. Eight percent (n = 134) of the sample reported the use of at least one of the six illicit drugs under investigation (ecstasy, cannabis, cocaine, meth/amphetamine, ketamine and GHB) in the past year. Having been offered or having had the opportunity to use illicit drugs in the past year, knowing other athletes who use drugs and identifying as a `full-time athlete` were significant predictors of past-year illicit drug use, while having completed secondary education or a post-school qualification was associated with a lower likelihood of past-year illicit drug use. Athletes are part of a sportsnet that includes family, coaches, support staff and other athletes, and these relationships may encourage the use, supply and demand for drugs. The current findings suggest that relationships with some of those in the sportsnet may play an important role when understanding illicit drug use among elite athletes. As education appears to be associated with a lower likelihood of illicit drug use among this group, initiatives should encourage athletes to engage in off-field pursuits which may also help prepare them for life after sport.